The coaching process : principles and practices for sport - Cross, Neville; Lyle, John. (Oxford : Butterworth Heinemann, 2002)
Discussing the various elements of the coaching process, this book takes an interdisciplinary approach to maximizing sports performance whilst avoiding common problems
Includes indexes and bibliographical references.
Keywords: Coaching (Athletics) Coach-athlete relationships; Entraînement (Sports)